The Hegemonization and Counter-Hegemonization of Polish Copyright Discourses - Radomska, Ewa (Qualitative Sociology Review, 2024)
This article explores the nature and structure of Polish discourses on copyright, specifically revealing to what extent social conflict over copyright is visible within these discourses and presenting the most important parties in this conflict. Following Ernesto Laclau and Chantal Mouffe’s discursive reconstruction of the hegemony, the article indicates that Polish copyright discourses are structured by an alternating sequence of discursive hegemonic and counter-hegemonic practices. The article specifies the most important logic applied within discursive battles over copyright by deconstructing the central dualities visible in Polish copyright debates. Hegemonization and counter-hegemonization of the discourses are indicated based on the discourse analysis of the Polish public debate on copyright and a qualitative analysis of in-depth interviews and focus group interviews with representatives of selected parties in the social conflict over copyright.